Sistem Pendukung Keputusan Analisa Kinerja Tenaga Honorer Menerapkan Metode WP pada Dinas Pendidikan Kabupaten Deli Serdang - Asia Arinanda Singarimbun; Mesran Mesran; Sarwandi Sarwandi; Meryance V Siagian; Bister Purba (JITEKH, 2021)
Government agencies, of course, have honorary staff. The honorary staff in its development aims to assist the performance of Civil Servants (PNS) where civil servants are already overwhelmed in carrying out the functions of the local government, one of which is in public services. Civil servants and honorary staff have an important role for the community in providing maximum public services, especially in the Deli Serdang Regency Education Office. In the process of realizing these services, the Education Office analyzes the performance of the honorary staff. The scopes to be analyzed include attendance, work discipline, cooperation, public services and other supporting factors. In the assessment process, an effective system is needed to see the results of the performance of the honorary staff, so a Decision Support System is needed to see these results. In this study the author uses a Decision Support System for Performance Analysis of Honorary Personnel at the Education Office of Deli Serdang Regency by applying the Weighted Product (WP) method. In this study, the authors also ranked the sample of honorary workers through the criteria listed to determine honorary workers who are entitled to an extension of their tenure.